1993
DOI: 10.1111/j.1365-2621.1993.tb03236.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Mapping in a Model Food Gel using Magnetic Resonance Imaging

Abstract: Two dimensional temperature maps of a model food gel (agar, microcrystalline cellulose, and water, 1.95:6.55:200), were obtained by MRI during heating and cooling. The molecular pseudo self-diffusion coefficient of water was used as a temperature indicator. A two dimensional Fourier transform spin-echo imaging sequence was used for data acquisition. The self-diffusion coefficient at room temperature was 1.26 x 1O-3 mm2/sec. Two dimensional self-diffusion images were obtained, and temperature images were calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(5 citation statements)
references
References 13 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…For MCC (m 0 = 6:6933 × 10 −6 kg), only one di usion coe cient was reported in the literature (D s = 1:26 × 10 −9 m 2 s −1 from Sun et al, 1993), but no mention was made of the conditions of the experiment. However the results are better than for Kaolin ( Figs.…”
Section: Internal Mass Transfermentioning
confidence: 99%
“…For MCC (m 0 = 6:6933 × 10 −6 kg), only one di usion coe cient was reported in the literature (D s = 1:26 × 10 −9 m 2 s −1 from Sun et al, 1993), but no mention was made of the conditions of the experiment. However the results are better than for Kaolin ( Figs.…”
Section: Internal Mass Transfermentioning
confidence: 99%
“…Those measurements are based on the sensitivity of water proton MRI parameters to temperature, including the chemical shift (Hall & Talagala, 1985), diffusion coefficient and relaxation times T1 (Doran et al ., 1994) and T2 (Jezzard et al ., 1992). More recently it has been suggested that MRI could be used to optimize industrial food processing that involves temperature (Sun et al ., 1993; Sun et al ., 1994; Hulbert et al ., 1995; Hulbert et al ., 1997; Ruan et al ., 1998a; Ruan et al ., 1998b); however, the MRI parameters used in those papers are not only temperature dependent but may also reflect structural changes in the food matrix. In contrast, phase mapping, which uses the sensitivity of chemical shift to temperature, is less dependent on the structural‐ and, to a certain extent, compositional heterogeneity in water‐based foodstuffs.…”
Section: Mrimentioning
confidence: 99%
“…There are two main reasons, namely (i) the increasing interest in dynamical quantities of Ñuid systems and their activation parameters1 and (ii) the possible use of self-di †usion coefficients for the indirect measurement of local temperatures (temperature mapping) in magnetic resonance imaging (MRI) experiments. 2 The main advantages of PFG NMR di †usion methods over conventional isotopic tracer methods are : fast measurements, small sample volumes, determination of "" true ÏÏ self-di †usion coefficients (which are not inÑuenced by interfering isotope e †ects) and an easy application to a wide pressure and temperature range. However, up to now tracer methods can be regarded as more accurate than PFG NMR methods and therefore the improvement of the precision of PFG NMR measurements is still an important aim.…”
Section: Introductionmentioning
confidence: 99%